Wskaźniki rozwoju społeczno-gospodarczego radzieckiej Gruzji - Piasny, Janusz (Wydział Prawa i Administracji UAM, 1969)
In 1968 there have passed forty seven years since the institution of Soviet authority in Georgia. During that time Georgia became transformed from an underdeveloped country into a leading republic of the Soviet Union. She has succeeded immensely in the development of industry and agriculture, developed the cultural life and raised considerably the living standard of the population. The industrial output in 1966 was 62 times higher than its level in 1913 and in the same time the agricultural output has been raised six times. Year in, year out the population was better satisfied with foodstuffs and industrial articles, the housing conditions and the cultural services were constantly improved. The consumption of foodstuffs and industrial articles was growing mainly in consequence of higher wages and lower prices of some basic groceries, whereas the improvement of housing and social and economic living conditions took place via the expanding benefits of the state and cooperative services (social consumption funds). Soviet Georgia has great achievements in the development of health-protection and education services. For every 10 000 residents there are 35 physicians, 83 persons of medical custodial staff, and 167 students — that sets Georgia in this respect in the very front rank of the world.
Indicators of Socio-Economie Development in Soviet Georgia